Digitizing PKK Administration Management in Patengan Village, Rancabali District, Bandung Regency - Indrianie, Mona; Mariane, Ine (Jurnal Pengabdian Masyarakat Formosa, 2024)
Digitizing Administration Management is an improvement in institutional administration management. The lack of orderly administration among PKK (Family Welfare Empowerment) cadres has become an important issue in the Master Plan of the PKK Movement for 2021-2024. Based on this, there is a need for efficiency, accuracy, and accessibility of administrative information. Therefore, the digitalization of administration systems is crucial to enhancing institutional administration. The partner in this community service activity is the PKK (Family Welfare Empowerment) cadres in Patengan Village, located in Rancabali District, Bandung Regency. The focus of the activity is to provide socialization on the Digitalization of PKK Administration Management. The main problems faced by the partners include inadequate infrastructure and facilities to support digitalization, as well as a lack of understanding about digitalization. Given this situation, we aim to provide understanding through socialization about digital administration. Based on the analysis, the target outcome is to increase knowledge, understanding, and skills in utilizing digitalization systems in PKK administration. This will help ensure that PKK administration in Patengan Village is well-organized and continues to develop.